Exploring the Beliefs about Language Learning among Undergraduate Engineering Students - Abd Majid, Siti Norzaimalina; Ismail, Rosnani (AJELP: Asian Journal of English Language and Pedagogy, 2024)
One of the components that contribute to learners’ effectiveness in language learning classrooms is their beliefs and notions about language learning. Beliefs about language learning are viewed as the presumptions or assumptions that students hold about their attitudes, motivations, learning strategies, and language learning styles. Engineering students may have different beliefs in contrast with other subjects due to the nature of their work, which focuses more on the scientific and technical parts. Furthermore, the employer always raised the issue that these engineers lack English language skills, which may stem from their beliefs. Thus, in this descriptive study, we intend to examine the engineering students’ beliefs about language learning based on a questionnaire of 34 items developed by Horwitz (1987). This quantitative study involved 258 engineering students in one public university in Malaysia, comprised of 181 males and 77 females. There were five major areas in assessing students’ beliefs namely: foreign language aptitude, the difficulty of language learning, the nature of language learning, learning and communication strategies, and motivations and expectations. Based on the findings, engineering students have strong beliefs that motivations and expectations in language learning are the most important factors in their learning process. To support them in improving their language learning, it is important to tailor programs to their specific needs and integrate technical content with language learning activities. Emphasising motivation and expectations is crucial, alongside addressing misconceptions about language learning and collaborating with employers to align language proficiency with industry needs are also key steps.